A perspectiva emocional das/os filhas/os que passaram pelo processo de filiação adotiva: desvendando seus sentimentos e suas histórias - Susana Maria de Souza Moraes Borges (2025)
The themes "adoptive emotion" and "adoptive children's feelings" were not found in the literature while major research objects, the same has not occurred for the adopters, who have been the subjects of countless studies targeting their emotions and feelings. Aiming to fill this void, arose the necessity of performing this current research, which aims to understand the feelings that these children present as a result of the adoption process, and the necessary mediations required to access their histories before adoption, aiming to understand the repercussions that this measure provokes on children and teenagers, through the reports of adult adoptees. This way, a qualitative and exploratory research was performed, as well as a bibliographic research, and open interviews through the life story technique with adult subjects, who can currently talk about their experiences as adoptees with a greater emotional security, being able to present and review their experiences regarding the adoption process. These individuals were also able to reveal their experiences regarding access to their origin and history before adoption, and present the consequences of the adoptive experience in their biopsychosocial development